Pemikiran Muhammad Al-Ghazali Dalam Studi Hadis: Telaah Kritis atas Kitab Al-Sunnah al-Nabawiyah Baina Ahl al-Fiqh wa Ahl al-Hadits - Handoko, Wahyu Ramdan Tri; Askar, Romlah Abubakar; Suparta, M (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the thoughts of Muhammad al-Ghazali in the study of hadith through an analysis of his monumental work Al-Sunnah al-Nabawiyah Baina Ahl al-Fiqh wa Ahl al-Hadits. Al-Ghazali proposed a new approach to understanding hadith by prioritizing the values of the Qur’an, maqasid al-shariah, and considerations of reason and social context. This research method uses a qualitative approach with literature study as the main method. The results of the study show that Al-Ghazali criticized the textualist approach that often ignores the moral and rational essence of Islamic teachings, and proposed a reconstruction of a more integrative and contextual methodology for understanding hadith.